The Factors Affecting Tax Aggressiveness Case Study of Manufacturing Companies Listed on the IDX - Wati, Asnandi; Astuti, Tutut Dewi (Golden Ratio of Data in Summary, 2025)
Tax aggressiveness is the engineering of taxable income through tax planning efforts by a company, either by using legal tactics (tax avoidance) or criminal (tax evasion). The purpose of this study is to examine the factors that affect tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The variables used in this study are company size, corporate governance, liquidity, leverage, and fixed asset intensity. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2020 to 2022. The sample of this study was selected using the purposive sampling method and data were taken from 13 samples. The results of this study show that the size of the company, corporate governance, has a significant effect on tax aggressiveness. Leverage, the intensity of fixed assets, affects tax aggressiveness. Meanwhile, liquidity has no effect on tax aggressiveness.